2017
DOI: 10.1159/000456111
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Low Ambient Temperature-Induced Myocardial Hypertrophy by Atorvastatin via Promoting Bcl-2 Expression

Abstract: Background/Aims: It is well documented that myocardial hypertrophy is associated with low ambient temperature. Atorvastatin (Atv) has been shown to protect against atherosclerosis, cardiac fibrosis, ischemia/reperfusion injury, etc. In this study, we aim to determine whether atorvastatin is effective in the treatment of myocardial hypertrophy induced by cold exposure and to shed light on underlying mechanism. Methods: The mice aged 4-week were randomized to Control (Ctl) group (raised at room temperature), Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…A major intrinsic feature of fibrosis is increased cardiac collagen deposition [26][27][28][29]. In this study, we observed that Aur administration largely reduced the expression of collagen type I in pressure-overloaded hearts and cardiac fibroblasts induced by Ang II treatment, which suggested that blockade of cardiac fibroblast activation is a critical mechanism for Aur-mediated inhibition of the progression to cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 54%
“…A major intrinsic feature of fibrosis is increased cardiac collagen deposition [26][27][28][29]. In this study, we observed that Aur administration largely reduced the expression of collagen type I in pressure-overloaded hearts and cardiac fibroblasts induced by Ang II treatment, which suggested that blockade of cardiac fibroblast activation is a critical mechanism for Aur-mediated inhibition of the progression to cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 54%
“…Myocardial apoptosis is one of the characteristics of pathological myocardial hypertrophy and contributes to the transition from compensatory hypertrophy to heart failure [23, 24]. Thus, the protective effect of atorvastatin on hypertrophic myocardium might be at least partly attributed to the inhibition of apoptosis [25]. Although there was no sign of heart failure at the age of 16 weeks in SHR in the present study, the inhibition of apoptosis by atorvastatin also had an important protective effect against the further progress of pathological myocardial hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al indicated that atorvastatin attenuated cardiac hypertrophy under cold exposure. 28 In another study, Wang et al demonstrated that pressure overload-induced right ventricular hypertrophy was reversed by the atorvastatin treatment. 29 Moreover, one study also showed an inhibitory effect of atorvastatin on hypertrophy caused by parathyroid hormone 1-34.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, in this study, atorvastatin reversed the hypertrophy induced by volume overload and stretch. Liang et al indicated that atorvastatin attenuated cardiac hypertrophy under cold exposure . In another study, Wang et al demonstrated that pressure overload‐induced right ventricular hypertrophy was reversed by the atorvastatin treatment .…”
Section: Discussionmentioning
confidence: 99%